2012
DOI: 10.1136/bjophthalmol-2012-301865
|View full text |Cite
|
Sign up to set email alerts
|

Effect of refractive status on peripapillary retinal nerve fibre layer thickness: a study by RTVue spectral domain optical coherence tomography

Abstract: We have shown that axial length/refractive status affected the peripapillary RNFL thickness profile measured by RTVue OCT. To make a correct diagnosis for glaucoma, either the axial length-induced magnification effect should corrected by ophthalmologists or the RTVue OCT database should be improved by taking axial length into account.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
37
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 24 publications
1
37
1
Order By: Relevance
“…Both the SAP sensitivity and cpRNFLT could have been influenced by the high myopia. [37][38][39] Finally, this cross-sectional retrospective study could not evaluate the intersession variability of each VF or cpRNFLT cluster values. To overcome these limitations, future prospective studies with larger sample sizes and strict inclusion criteria are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Both the SAP sensitivity and cpRNFLT could have been influenced by the high myopia. [37][38][39] Finally, this cross-sectional retrospective study could not evaluate the intersession variability of each VF or cpRNFLT cluster values. To overcome these limitations, future prospective studies with larger sample sizes and strict inclusion criteria are needed.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Oner et al (12) evaluated the RNFL thickness in myopic and emmetropic eyes by SD-OCT and observed that the overall global RNFL thickness of myopic eyes was significantly thinner than that of emmetropic eyes. A study by Table III.…”
Section: Discussionmentioning
confidence: 99%
“…2 Wang et al 3 revealed that magni¯cation attributable to axial length (AL) and refractive error has minimal impact on measurements of macular and RNFL thickness in 120 children, but they asserted that transverse measurements such as optic disc diameter should be corrected by magni¯cation effect. However, other studies conducted in adults 4,5 and children 6,7 found that AL [4][5][6][7] and refractive error 5,6,8 in°uence the measurements of OCT. The studies mentioned earlier [4][5][6][7][8] referred that AL-related ocular magni¯cation should be taken into account to ensure better accuracy in the measurements made with OCT.…”
Section: Introductionmentioning
confidence: 94%
“…However, other studies conducted in adults 4,5 and children 6,7 found that AL [4][5][6][7] and refractive error 5,6,8 in°uence the measurements of OCT. The studies mentioned earlier [4][5][6][7][8] referred that AL-related ocular magni¯cation should be taken into account to ensure better accuracy in the measurements made with OCT. Previous studies used time domain OCT (Stratus OCT); however, spectral domain (SD-OCT) such as Cirrus HD-OCT o®ers a higher axial resolution and scanning speed than conventional time-domain techniques.…”
Section: Introductionmentioning
confidence: 94%